Hutabolon Village Community Behavior in Overcoming Health Problems - Rholand Muary; Agung Suharyanto; Onggal Sihite; Wiflihani; Jamilah Nasution (Britain International for Academic Research (BIAR-Publisher), 2020)
The behavior of the Hutabolon Village community in overcoming the problem of diseases that occur or that they experience is still relatively moderate. The community is already aware of the importance of health, but because there are insufficient facilities or health facilities, it makes the community still have a little difficulty in getting treatment. The research method used is qualitative with a descriptive approach, through this research method researchers get information about the types of diseases that often occur, modern and traditional medicine carried out by the people in Hutabolon Village as a behavior in overcoming health problems. The results of the study concluded that the types of diseases that often occur in Hutabolon Village are eight such as flu or respiratory infections, fever, rheumatism, diarrhea, wounds or vulnus, cavities or toothache, acute respiratory infections, and stomach acid. Behavior of the people of Hutabolon Village To overcome the problem of the disease is to use modern medicine or medical services coupled with traditional medicine.